Ferroelectric polarization reversals in C2N/α-In2Se3 van der Waals heterostructures: a conversion from the traditional type-II to S-scheme - Zhong, Yongle (Frontiers in Chemistry, 2023)
Introduction: Ferroelectric substances, characterized by inherent spontaneous polarization, can boost photocatalytic efficiency by facilitating the separation of photogenerated carriers. However, conventional photocatalysts with perovskite-class ferroelectricity are generally constrained by their 3D arrangement, leading to less accessible active sites for catalysis and a smaller specific surface area compared to a 2D layout. Methods: In my research, I developed a 2D ferroelectric heterostructure consisting of C2N/α-In2Se3. I performed first-principle calculations on the 2D C2N/α-In2Se3 heterostructure, specifically varying the out-of-plane ferroelectric polarization directions. I primarily focused on C2N/α-In2Se3 (I) and C2N/α-In2Se3 (II) heterostructures. Results: My findings revealed that reversing the ferroelectric polarization of the 2D α-In2Se3 layer in the heterostructures led to a transition from the conventional type-II [C2N/α-In2Se3 (I)] to an S-scheme [C2N/α-In2Se3 (II)]. The S-scheme heterostructure [C2N/α-In2Se3 (II)] demonstrated a high optical absorption rate of 17% in visible light, marking it as a promising photocatalytic material. Discussion: This research underscores the significance of ferroelectric polarization in facilitating charge transfer within heterogeneous structures. It provides a theoretical perspective for developing enhanced S-scheme photocatalysts, highlighting the potential of 2D ferroelectric heterostructures in photocatalytic applications.